Genetic analysis of tropical Beauveria and Metarhizium associated with sugar cane insects - Vargas-Martínez, Alejandro (2019)
Introduction. Entomopathogenic fungi are used as biopesticides to control invertebrate pests in agriculture. The generation of genetic information and its geographic relationships are important for diversity studies and for the protection of biological resources. Objective. The aim of this study was to analyze the allelic diversity and the genetic and geographic relationships of several isolates of Beauveria and Metarhizium from Departamento de Investigación y Extensión de la Caña de Azúcar (DIECA) of Liga Agrícola Industrial de la Caña de Azúcar (LAICA). Materials and methods. This research was performed in DIECA and Universidad Nacional in 2014 and 2015. Fourteen and thirteen isolates of Beauveria and Metarhizium, respectively, were cultured from various Hymenoptera and Coleoptera insects of Costa Rica and Brazil. The isolates were analyzed using primer pairs that amplified simple sequence repeat (SSR) markers; twelve specific to Beauveria and thirteen specific to Metarhizium. Geographic and genetic correlation matrices were tested using a Mantel test. Results. All Beauveria primer pairs generated products, while only eight of the thirteen Metarhizium pairs generated products. Several sets of Beauveria primers were highly informative, but only one of the pairs was moderately informative in Metarhizium. Five Beauveria primer pairs generated unique genetic profiles in eight of the fourteen isolates (57%). Genetic relationships revealed two major clades among the Beauveria isolates, where one of these clades separated into two smaller groups. Metarhizium isolates were closely related, except for one (Mal12). A linear model explained 26% of the variability of the correlation between the genetic distances and the geographic distances found in Beauveria isolates, however, no relationships were found in Metarhizium isolates. Conclusion. A greater number of markers or different molecular marker technologies would be necessary to distinguish the isolates from the collection. The information in this work is useful for diversity studies and protection of intellectual property. Herein, we also consider search strategies to encounter diverse fungi.